2020
DOI: 10.1055/s-0040-1719119
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Narrow-band Imaging on the Pre- and Intra- operative Assessments of Neoplastic and Preneoplastic Laryngeal Lesions. A Systematic Review

Abstract: Introduction Narrow-band imaging is an endoscopic diagnostic tool that, focusing on superficial vascular changes, is useful to detect suspicious laryngeal lesions, enabling their complete excision with safe and tailored resection margins. Objectives To analyze the applications and benefits of narrow-band imaging in detecting premalignant and malignant laryngeal lesions through a comparison with white-light endoscopy. Data Synthesis A literature search was performed in the PubMed, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Because of this, Lin et al concluded that NBI is not suitable for diagnosing papillomatosis. On the contrary, NBI SP was better in the case of LP (92–100%) than in the case of LSCC (65–82%), showing another NBI limitation: white plaque that may cover the lesion and lead to false negative [ 6 ]. Only one study reported PPV and NPV data, 52.82% and 86.79% for LP and 91.14% and 68.18% for LSCC, respectively [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of this, Lin et al concluded that NBI is not suitable for diagnosing papillomatosis. On the contrary, NBI SP was better in the case of LP (92–100%) than in the case of LSCC (65–82%), showing another NBI limitation: white plaque that may cover the lesion and lead to false negative [ 6 ]. Only one study reported PPV and NPV data, 52.82% and 86.79% for LP and 91.14% and 68.18% for LSCC, respectively [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Malignant lesions are characterized by enlarged, brownish vessels, and IPCLs are destroyed with tortuous shape (IPCLs type V) [ 5 ]. Several studies demonstrated the high sensitivity and NPV of type V pattern for detecting early glottic cancer [ 15 , 16 , 17 ]; carcinogenesis is related to blood vessel changes and angiogenesis [ 18 ]. However, LP is also characterized by a type V pattern on NBI, and this may lead to misdiagnosis, as reported by all the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human papillomavirus (HPV) is a sexually transmitted virus and is the leading cause of uterine cervical cancer [ 1 ]. In recent decades, its growing main role in the onset of oral and oropharyngeal carcinoma (OPC) was studied [ 2 ]. In fact, there is a reduction in the incidence of OPC due to smoking and/or alcohol.…”
Section: Introductionmentioning
confidence: 99%